Efektifitas Kombinasi Aerobic Low Impact dengan Stretching Exercise terhadap Peningkatan Kualitas Hidup pada Ibu dengan Keluhan Muskuloskeletal di Dusun Ngegot Desa Selokaton Gondangrejo Karanganyar - Rina Kurnia; Lis Sarwi Hastuti (Poltekkes Kemenkes Surakarta, 2020)
Background: Musculoskeletal complaints are discomforts to the pain experienced by someone that is triggered by a body that receives statistics, or performs activities in a less ergonomic position repeatedly for a long time. One result of musculoskeletal is a decrease in quality of life. Efforts that can be made to improve the quality of life with musculoskeletal complaints are a combination of low-impact aerobics with routine stretching exercises. This study aims to determine the effectiveness of Aerobic Low Impact with Stretching Exercise on the Quality of Life of Mothers with Musculoskeletal Complaints in Ngegot Selokaton Gondangrejo Karanganyar Hamlet. Methods: The design of this study was a pretest-posttest pre experimental design. Sampling was done by purposive sampling technique. Quality of life complaints data was taken using the WHOQOL-BREF instrument. Results: The results of research through the Wilcoxon statistical test and paired t-test on the domain of quality of life obtained the same results, namely p value = 0.001. Conclusion: The combination of low impact aerobics with stretching exercises is effective to improve the quality of life of mothers with musculoskeletal complaints about Ngegot Selokaton village. Gondangrejo Karanganyar sees from 4 domains of quality of life on the WHOQOL-BREF instrument (health, psychological, social, social, and social)